Performance Comparison of Circular Patch Antennas Using Three Different Substrates at mmWave for 5G Systems - Aldrewy, Siraj Aldeen M.; Almazok, Salem A.; Mami, Ali O. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study presents the design and analysis of three inset-fed circular patch antennas using different substrate materials with unique dielectric constants, namely Polycarbonate, Preperm 260 LDS, and Rogers RT-5880 to compare their performance. The proposed designs utilize copper material for the radiating patch on the top side of the dielectric substrate and the ground plane on the bottom side of the same dielectric substrate. These structures resonate at a frequency of 28 GHz, and the dimensions of the three antenna structures were computed for the three different substrate materials. The performance of the three designs was simulated using the Computer Simulation Technology (CST) software to compare their performances. The performance parameters utilized to evaluate and compare the proposed designs include return loss, gain, radiation efficiency, bandwidth, radiation pattern, and voltage standing wave ratio. The proposed structures provide a return loss (S11) less than -10 dB, and their VSWR was very close to the ideal value, which is less than two for practical wireless applications. Moreover, Preperm 260 LDS exhibited better results in terms of S11 and VSWR, with values of -61.038 dB and 1.0017, respectively. In terms of gain, it increases when low-dielectric constant materials are employed.